Flow in porous rocks : energy and environmental applications - Woods, Andrew W. (Cambridge : Cambridge University Press, 2015)
Focusing on simplified models of physical flow processes, this book develops a series of quantitative models to describe the recovery of oil and gas from hydrocarbon reservoirs (including fracking), the physics of geo-sequestration of CO2, geothermal power production, and the potential for underground contaminant dispersal in the long-term storage of nuclear waste. The author approaches these problems by developing simplified mathematical models and identifying the key dimensionless variables that control the processes. This analysis is then used to demonstrate the challenges and constraints of modelling flow in complex and heterogeneous rocks, which often have uncertain flow properties. Analytical solutions for flows are provided where possible, and analogue laboratory experiments are also presented to help illustrate and provide a different perspective on the flows. Incorporating end-of-chapter exercises, this is an important introduction to the different controls on flow in porous rocks for academic researchers, energy industry professionals and graduate students.
1. Introduction -- 2. Porous rocks -- 3. Flow in porous rocks -- 4. Accounting for uncertainty -- 5. Dispersion in porous media -- 6. Frontal instability -- 7. Two-phase flow -- 8. Fluid-rock interactions -- 9. Gravity-driven flow in porous media -- 10. Buoyancy effects on dispersion -- 11. Geothermal power and heat storage -- 12. Compressibility and gas flows -- 13. Epilogue.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Fluids -- Migration; Rocks -- Permeability -- Mathematical models; Porous materials -- Fluid dynamics; Petroleum -- Geology